Trypanosoma cruzi: the expansion of NK, T, and NKT cells in the experimental infection - Antúnez, María Inés (2004)
Fil: Antúnez, María Inés. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.